BORROWING WORDS IN UZBEK AND ENGLISH: A CONTRASTIVE STUDY - Abdusadikova Dilfuza Abduvayit qizi; Radjabov Nasir Nasimovich (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article explores the process by which foreign words penetrate and become established within the lexical systems of Uzbek and English, tracing the degree to which such words are structurally assimilated and identifying the conditions that determine whether a borrowed item achieves full integration or remains marked as external. Rather than cataloguing loanwords by origin, the study focuses on the dynamic relationship between external linguistic pressure and the internal structural resistance of each receiving language. The article argues that the degree and character of  lexical  assimilation  is  shaped  not  only  by  phonological  and  morphological compatibility but equally by the social prestige attached to the donor language, the institutional context of contact, and the communicative domains in which borrowed words first circulate. Findings from both languages reveal that the boundary between native  and  borrowed  vocabulary  is  far  less  stable  than  traditional  lexicological classifications suggest.